Effects of (+)- catechin + quercetin usage before exhaustion exercise on free radical and antioxidant enzyme levels: (+)- catechin + quercetin usage before Exhaustion Exercise - Durukan, Erdil (Progress in Nutrition, 2020)
Study Objectives: The aim of this study was to determine the effects of the use of (+) -Catechin + Quercetin for 10 days before an exhaustion exercise on free radical and antioxidant enzyme levels. Methods: The study was performed on 12 male Wistar rats (260-320 gr.) from the same family and animals divided into two groups as a control and experimental group. After the first exhaustion exercise, rats in the experimental group used (+)- Catechin + Quercetin in addition to the standard laboratory diet and they performed the second exhaustion exercise. In the experimental group, 20 mg / kg (+) - Catechin + Quercetin substances were dissolved in dimethyl sulfoxide and given 1 ml / kg while the control group received 1 ml / kg 0.05% dimethyl sulfoxide by gavage in addition to standard laboratory diet daily for 10 days. SOD, CAT, GPx, GST, and MDA levels were measured by spectrophotometer. The IBM SPSS Statistics 24.0 was preferred for the statistical analysis. The repeated measures two-factor variance analysis was used to determine the difference between control and experimental groups. Results: It was determined that antioxidant enzyme levels (SOD, CAT, GPx, and GST levels) in rats using (+) - Catechin + Quercetin for 10 days before an exhaustion exercise were higher than those of the control group. Despite that, it was determined that MDA levels in rats using (+) - Catechin + Quercetin for 10 days before an exhaustion exercise were lower than those of the control group. Conclusion: It can be said that the use of (+)- Catechin + Quercetin can reduce the amount of MDA which is the end product of lipid peroxidation in exercise and may create a protective effect against free radicals and increase the levels of antioxidant enzymes and strengthen the antioxidant defense systems of the cells and have a positive effect on exercise performance.